1979
DOI: 10.1111/j.1471-4159.1979.tb02276.x
|View full text |Cite
|
Sign up to set email alerts
|

HETEROGENEITY OF HISTAMINE Hi‐RECEPTORS: SPECIES VARIATIONS IN [3H]MEPYRAMINE BINDING OF BRAIN MEMBRANES

Abstract: Abstract[3H]Mepyramine binds with high affinity to membranes from brain of human, rat, guinea‐pig, rabbit and mouse with drug specificity indicating an association with histamine H1receptors. Considerable species differences occur in the affinity of [3H]mepyramine, with guinea‐pig and human having 34 times greater affinity than rat, mouse or rabbit. The greater affinity of [3H]mepyramine in guinea‐pig than in rat is attributable both to faster association and slower dissociation rates in guinea‐pig. Species di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
65
2

Year Published

1985
1985
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(80 citation statements)
references
References 19 publications
13
65
2
Order By: Relevance
“…Marked differences between the activity of the enantiomers have also been observed in rabbit aorta (O'Neill & Patil, 1975 (Hill et al, 1978;Tran et al, 1978;Chang et al, 1979;Quach et al, 1980). It is of interest that there are no marked species differences in stereoselectivity ratios, even though the ability of chlorpheniramine to displace the labelled ligand varies (Chang et al, 1979). Dimethindene is a potent H, antihistamine, with activity similar to or greater than that of (+)-chlorpheniramine in a number of tests of histamine receptor function (Barrett et al, 1961) and in receptor binding studies (Tran et al, 1978;Kubo et al, 1987). Its stereoselectivity with respect to H1 sites is less well documented, but (-)-dimethindene is between 20 and 100 times more potent than the (+)-isomer in blocking the response to histamine receptor activation in various guineapig tissue preparations (Borchard et al, 1985).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Marked differences between the activity of the enantiomers have also been observed in rabbit aorta (O'Neill & Patil, 1975 (Hill et al, 1978;Tran et al, 1978;Chang et al, 1979;Quach et al, 1980). It is of interest that there are no marked species differences in stereoselectivity ratios, even though the ability of chlorpheniramine to displace the labelled ligand varies (Chang et al, 1979). Dimethindene is a potent H, antihistamine, with activity similar to or greater than that of (+)-chlorpheniramine in a number of tests of histamine receptor function (Barrett et al, 1961) and in receptor binding studies (Tran et al, 1978;Kubo et al, 1987). Its stereoselectivity with respect to H1 sites is less well documented, but (-)-dimethindene is between 20 and 100 times more potent than the (+)-isomer in blocking the response to histamine receptor activation in various guineapig tissue preparations (Borchard et al, 1985).…”
Section: Discussionmentioning
confidence: 96%
“…However, the affinities of the isomers for the Hl-receptor indicate a high degree of stereoselectivity (Chang et al, 1979;Borchard et al, 1985), and so studies with the enantiomers may help to resolve whether sedation is related specifically to the steric configuration and is due to Hl-receptor antagonism alone.…”
Section: Introductionmentioning
confidence: 99%
“…Our results support the notion that histamine H 1 receptors have distinct anatomic location and show striking differences in their density and regional distribution among different species. 11,29,30 Saturation binding revealed that in rat brain, B max was significantly higher in the tissue representing the rest of the brain. In contrast to B max , the K d value was similar in the two brain regions, suggesting that the receptors have similar affinity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the binding of [3H]-doxepin is complex and not all the data are consistent with the receptor heterogeneity explanation, as the authors note. Caution is also necessary in interpreting Hill coefficients < 1 obtained from inhibition of [3H]-mepyramine binding, since even moderate concentrations of the 3H-ligand appear to label secondary, non H,-receptor sites in both guinea-pig and rat tissues (Hill & Young, 1980;Hadfield et al, 1983 (Chang et al, 1979;Figge et al, 1979;Palacios et al, 1979;Coupet & Szuchs-Myers, 1981; Tran et al, 1981;Kanba & Richelson, 1983). A similar disagreement exists in rat brain, 1.4 x 109M`to 5.0X 10'0M-' (Tran et al, 1978(Tran et al, , 1981 i) The Macmillan Press Ltd 1985 Richelson, 1980;, but in this species there is a further difficulty in that there is no reported affinity constant for doxepin derived from inhibition of a functional response mediated by Hi-receptors in an intact tissue preparation.…”
Section: Introductionmentioning
confidence: 99%